Exploring experiences of poor Malay single mothers : how they perceive and manage their daily life. - Hasanah Hassan. (2013)
This paper aims to explore the experiences of poor Malay single mothers with young children and teenagers, with respect to how they perceive and manage their daily life in Singapore. By looking at the intersection between class, gender and ethnicity, one is able to understand their experiences more comprehensively. The reason for doing this is that despite their prevalence and increasing number, there has not been any bottom-up approach to understand the perspective of this group of people. This study is important to fill the literature gap and to gain insights as to why the poverty circle within the Malay community is a vicious one. This is achieved by interviewing eight Malay single mothers. The findings highlight the sense of helplessness that these women experience, and how they manage it by being contented. Also, another evident theme is the reproduction of class in the lives of their children.